2002
DOI: 10.1038/sj.leu.2402511
|View full text |Cite
|
Sign up to set email alerts
|

mRNA-electroporated mature dendritic cells retain transgene expression, phenotypical properties and stimulatory capacity after cryopreservation

Abstract: Genetically modified dendritic cells (DC) are increasingly used in vitro to activate cytotoxic T lymphocyte (CTL) immune responses. Because T cell activation protocols consist of multiple restimulation cycles of peripheral blood lymphocytes with antigen-loaded mature DC, continuous generation of DC is needed throughout the experiment. Therefore, cryopreservation of DC loaded with antigen is a valuable alternative for weekly generation and modification of DC. Recently, we described an antigen loading method for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
44
1
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 13 publications
1
44
1
2
Order By: Relevance
“…6, cell viability was high, and Ag was still detectable in the DC 2 days after the initial electroporation in virtually all cells when using this strategy. Compared with our previous results (20,29), related to the electroporation of DC cultured in serum in the presence of GM-CSF and IL-4, the level of protein expression, e.g., EGFP, was much lower in monocytes after 24 h (data not shown) and 48 h (Fig. 6C).…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…6, cell viability was high, and Ag was still detectable in the DC 2 days after the initial electroporation in virtually all cells when using this strategy. Compared with our previous results (20,29), related to the electroporation of DC cultured in serum in the presence of GM-CSF and IL-4, the level of protein expression, e.g., EGFP, was much lower in monocytes after 24 h (data not shown) and 48 h (Fig. 6C).…”
Section: Discussioncontrasting
confidence: 88%
“…This transfection technology resulted in high level transgene expression in Mo-DC using an EGFP reporter gene. More than 70% of the transfected cells showed high level EGFP expression (relative fluorescence between 10 2 and 10 3 decade as measured by flow cytometry) and retained their phenotypical properties after transfection (20,29). However, the use of this technology for transfection of short term, serum-free cultured DC, as presented in this study, resulted in substantial cell mortality among transfected cells (data not shown).…”
Section: Discussionmentioning
confidence: 65%
“…[24][25][26][27] Recently, mRNA electroporation of human monocyte-derived DC was described as a very efficient tool, without the need for viral vectors. 34,[36][37][38] Here, we further expand on the method of mRNA electroporation of human monocyte-derived DC. This procedure is considered to be very safe, because the mRNA has a short half-life in the cells, and is not integrated into the genome of the cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports described that mRNA electroporation does not influence DC viability, DC phenotype or allo-stimulatory capacity. 34,[36][37][38] We show that the transgene expression level can be modulated by varying the amount of mRNA used for electroporation. mRNA-electroporated DC can respond to CD40 ligation by IL-12 secretion, albeit slightly reduced compared to non-or mock-electroporated DC.…”
mentioning
confidence: 92%
“…2,3 Directly after electroporation, ES cells were further cultured in standard ES cell medium supplemented with leukemia inhibitory factor (LIF). After 6 h of culture, cells were analysed by fluorescence microscopy in order to detect EGFP-positive cells.…”
mentioning
confidence: 99%